The Relevance of the Character of Khulafaurrasisyidin to the Education of Tengka Madura - Intan Dwi Permatasari; Maimun, Maimun; Ach Syafiq Fahmi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to correlate the character of Khulfaurrasyidin with the Tengka education in Madura. This research uses the Library Research research method, namely a research method in which information is obtained by referring to books, journals, articles, newspapers, history books and so on. The results of this research state that firstly, the caliph Abu Bakar and his correlation to Tengka's education is his honest character in accordance with the caliph's nickname, namely